2017
DOI: 10.1371/journal.pone.0175953
|View full text |Cite
|
Sign up to set email alerts
|

Promoter hypermethylation as a mechanism for Lamin A/C silencing in a subset of neuroblastoma cells

Abstract: Nuclear lamins support the nuclear envelope and provide anchorage sites for chromatin. They are involved in DNA synthesis, transcription, and replication. It has previously been reported that the lack of Lamin A/C expression in lymphoma and leukaemia is due to CpG island promoter hypermethylation. Here, we provide evidence that Lamin A/C is silenced via this mechanism in a subset of neuroblastoma cells. Moreover, Lamin A/C expression can be restored with a demethylating agent. Importantly, Lamin A/C reintroduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 117 publications
2
18
1
Order By: Relevance
“…Specifically, is a representative measure of the elastic modulus of the nucleus and is a representative measure of the nuclear stretch modulus. We then find that our measured mean of 0.58 kPa corresponds to = 0.63 kPa and our measured mean of 0.79 kPa corresponds to = 2.5 mN/m, both of which are consistent with the current literature for Young's modulus measurements of the nucleus and stretch modulus of the nuclear membrane respectively (Dahl et al 2004;Dahl et al 2005;Mazumder et al 2008;Schape et al 2009;Liu et al 2014;Neubert et al 2018;Wang et al 2018;Rosso, Liashkovich, and Shahin 2019). Furthermore, we varied the size of our model nucleus and found that and are independent of initial nuclear size ( Figure S6), similar to our results from experiments ( Figure S3).…”
Section: Two-materials Finite Element Model Correlates Resistances To supporting
confidence: 91%
See 1 more Smart Citation
“…Specifically, is a representative measure of the elastic modulus of the nucleus and is a representative measure of the nuclear stretch modulus. We then find that our measured mean of 0.58 kPa corresponds to = 0.63 kPa and our measured mean of 0.79 kPa corresponds to = 2.5 mN/m, both of which are consistent with the current literature for Young's modulus measurements of the nucleus and stretch modulus of the nuclear membrane respectively (Dahl et al 2004;Dahl et al 2005;Mazumder et al 2008;Schape et al 2009;Liu et al 2014;Neubert et al 2018;Wang et al 2018;Rosso, Liashkovich, and Shahin 2019). Furthermore, we varied the size of our model nucleus and found that and are independent of initial nuclear size ( Figure S6), similar to our results from experiments ( Figure S3).…”
Section: Two-materials Finite Element Model Correlates Resistances To supporting
confidence: 91%
“…Nuclear mechanics are primarily dictated by the nuclear lamina and chromatin, as well as indirectly influenced by the cytoskeleton (Stephens, Banigan, and Marko 2019). The cytoskeleton protects the nucleus both through an actin cap (Khatau et al 2009;Haase et al 2016;Kim et al 2018) and a peri-nuclear cage of the intermediate filament vimentin (Neelam et al 2015;Patteson et al 2019;Rosso, Liashkovich, and Shahin 2019). The nuclear lamina, primarily lamin A/C, has consistently been shown to be a major mechanical constituent of the nucleus through constricted migration, micropipette aspiration, atomic force microscopy, micromanipulation, and other techniques (Dahl et al 2004;Lammerding et al 2004;Dahl et al 2005;Lammerding et al 2006;Lee et al 2007;Pajerowski et al 2007;Schape et al 2009;Swift et al 2013;Hanson et al 2015;Neelam et al 2015;Stephens et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Although an increasing number of reports recently implicated lamins in human cancers, their role in OS, the most common primary malignant neoplasia of the skeletal system [39], has been Interestingly, although 72 h mevinolin treatment reduced cell viability in all OS cell lines, the most significant effect of mevinolin was observed in MG63 cells, expressing the highest prelamin A levels (Figure 5a). Moreover, after long-term mevinolin treatment, the highest increase in the percentage of apoptotic cells was observed in MG63 cell culture (Figure 5b).…”
Section: Discussionmentioning
confidence: 94%
“…Although an increasing number of reports recently implicated lamins in human cancers, their role in OS, the most common primary malignant neoplasia of the skeletal system [39], has been elusive.…”
Section: Discussionmentioning
confidence: 99%
“…20 Neuroblastoma cells with silenced lamin A/C by hypermethylation display more aggressive behavior. 21 Lamin B1 expression is considerably increased in hepatocellular carcinoma and is related to the tumor size, tumor stage and the number of nodules. Increased plasma lamin B1 levels can also be used to predict hepatocellular carcinoma in the early stage.…”
Section: Discussionmentioning
confidence: 99%